Heat Shock Protein 90 (Hsp90) as a Molecular Target for the Development of Novel Drugs Against the Dermatophyte Trichophyton rubrum - Jacob, Tiago R.; Peres, Nalu T. A.; Martins, Maíra P.; Lang, Elza A. S.; Sanches, Pablo R.; Rossi, Antonio; Martinez-Rossi, Nilce M. (Frontiers in Microbiology, 2015)
Treatment of fungal infections is difficult due to several reasons, such as side effects of drugs, emergence of resistant strains, and limited number of molecular targets for the drug compounds. In fungi, heat shock proteins (HSP) have been implicated in several processes with the conserved molecular chaperone Hsp90 emerging as a potential target for antifungal therapy. It plays key cellular roles by eliciting molecular response to environmental changes, morphogenesis, antifungal resistance, and fungal pathogenicity. Here, we evaluated the transcription profiles of hsp genes of the most prevalent dermatophyte Trichophyton rubrum in response to different environmental challenges including nutrient availability, interaction with cells and molecules of the host tissue, and drug exposure. The results suggest that each HSP responds to a specific stress condition and that the cohort of HSPs facilitates fungal survival under various environmental challenges. Chemical inhibition of Hsp90 resulted in increased susceptibility of the fungus to itraconazole and micafungin, and decreased its growth in human nails in vitro. Moreover, some hsp and related genes were modulated by Hsp90 at the transcriptional level. We are suggesting a role of Hsp90 in the pathogenicity and drug susceptibility of T. rubrum as well as the regulation of other HSPs. The synergism observed between the inhibition of Hsp90 and the effect of itraconazole or micafungin in reducing the fungal growth is of great interest as a novel and potential strategy to treat dermatophytoses.